MEASURING THE IMPACT OF CO-WORKER SUPPORT ON JOB SATISFACTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR: AN ISLAMIC PERSPECTIVE - Mohd Soffian Lee, Umi Hamidaton; Ahmad, Nor Azima; Ismail, Anita; Muda, Farah Laili (I-iECONS e-proceedings, 2023)
The success of an organization also depends heavily on collaboration and knowledge sharing among team members. It is important that employees can count on the support of their colleagues, as this facilitates their functioning and coping with work demands, because the employee is one of the most valuable assets in an organization. Co-worker support plays an important role in the organization because an employee must cooperate and build a good teamwork with a colleague in order to achieve positive behavior among employees. Therefore, this study examines the relationship between co-worker support and employee behavior from an Islamic perspective as previous research has shown, co-worker support could have a significant impact on employee behavior in the workplace. In this study, a cross-sectional method was used. Data from 300 respondents working as government employees in Peninsular Malaysia were randomly collected and the Partial Least Squares Structural Equation Model (PLS-SEM) was used to assess the quality of the measurement model and test the hypotheses for the study model. The results of the structural equation model confirm that co-worker support is positively related to job satisfaction and organizational citizenship behavior. This result is an important recommendation for organization to understand the nature of employees and ensure the sustainability of the company in times of global economic competition.